The Influence of Digital Marketing on the Decision to Stay at a Syari'ah Homestay (Case Study: Ortega Syariah Homestay) - Rohsianti, Aprilia Dian; Almadani, Arziqna Nisa; Azizatustani, Mayada Wafiq; Hinawati, Titik (UM Purwokerto Press, 2025)
Sharia homestay is a form of accommodation that provides temporary housing for tourists by complying with Islamic sharia principles. This study aims to analyze the effect of digital marketing on the decision to stay at Homestay ortega svari'ah In the digital era, marketing through online platforms has become very important to attract consumers' attention, therefore it is important to understand how digital marketing elements, such as online visibility, social interaction, reviews, promotions, and educational content, influence consumer decisions. This research method uses quantitative methods and collects data by distributing questionnaires. This involves 30 respondents who are consumers who have stayed at the homestay. The questionnaire was designed to measure aspects of digital marketing such as Social Media, Search Engine Optimization (SEO), and Online Booking Platforms (OTA). The main variables analyzed include digital marketing strategies, such as the use of social media and OTA, and their impact on guests' stay decisions. Data analysis was carried out using multiple linear regression to determine the relationship between digital marketing variables and stay decisions. The results of the analysis show that digital marketing through social media (Instagram) and search engine optimization (SEO) have a positive effect on the decision to stay at a sharia homestay. This study recommends the development of digital marketing through email, which can be an effective strategy to reach potential consumers to reach potential guests, provide information about special offers, and build stronger relationships with customers.